The impact of relative age on sampling and performance in Swedish age-group swimming system - Buhre, T.; Tschernij, O. (The Sport Journal, 2019)
The phenomena of relative age effect (RAE) has been investigated thoroughly in the sport and school settings. However, different measures and research designs have been applied in the various settings. At the same time different constructs, such as sampling, participation, and performance have been investigated in separate studies. Most interpretations have been done in a de-contextualized manner. That is, results have not been interpreted based on the functioning of the age-grouping system over time, but rather on a general level of grouping individuals based on chronological age. The purpose of this study was to investigate the occurrence of RAE in sampling, competitive participation, and selection for national competition in the Swedish age-group swimming system based on a thorough understanding of the specific impacts of age and gender of this system over time.